PENERAPAN STRATEGI PEMBELAJARAN FIRE-UP UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 009 BINTAN TIMUR KABUPATEN BINTAN PROVINSI KEPULAUAN RIAU - Runi Santika; Syahrilfuddin Syahrilfuddin; Zufriady Zufriady (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research was motivated by the low results of fifth grade students learn math SDN 009 Bintan Timur, seen from the minimum completeness criteria (KKM) set the school is 75. Of the 25 students in a class, a total of 7 students (28%) reached KKM and 18 students (72%) who did not reach KKM with an average grade of 64.40. The purpose of this study was to improve mathematics learning outcomes SDN 009 Bintan Timur through the application of learning strategies of FIRE-UP. FIRE-UP learning strategy is a strategy that focuses on the child's thinking skills development efforts to process the information useful. This study was conducted in May 2018 were carried out in the first semester of 2017/2018. Taken the form of research is classroom action research (PTK). The study consisted of two cycles consisting of four meetings and two meetings of material daily tests. Mathematics learning outcome can be seen from the average on the basis of student's score is 64.40 with classical completeness 28% and then increased the daily test I with an average of 73.80 with classical completeness 48% with a percentage increase of 14.59% %. Then in the second daily test, the average test results increased to 83.40 with classical completeness 100% with a percentage increase of 29.50%. Activities of teachers in the first cycle of the first meeting of 63.63% and increased in the second meeting be 70.45%. At the first meeting of the second cycle of activity was up becoming 79.54% and at the last meeting be 81.81%, with both categories. Activity of students in the first cycle of the first meetings of 59,09% and increased in the second meeting be 68,18%. In the first meeting of the activity of students in the second cycle increased to 77,27 % and in the last encounter to be 79,54 % with good category.Keywords: FIRE-UP Learning Strategies, Mathematic learning result